(3GdEcdjd aj CfSGH MejQ hCjGe edhcgGs - (3GdMSf Hf CMeO Hf jYbhH GdgeOGfj , GHf GdMGFc , CHh eMeO,J (B334 (3g` s ((3jMi Hf Ydi Hf MSGf GdYPQi s)
(3ChdgG (B:s
(3GdcJGH GdKGef ef GdCcdjd hgh cJGH eMGaO Gdjef heSGfOgG GHH eG LGA ef PcQ bVjI Gdjef heYGbdgG heG bjd ajgG ef GdTYQ s
(3BNQgG (B:s
(3Ke NHQfi CHh GdYHGS Hf CHj ZGdH GdSdei CfgG KeGfhf SOkG hGdMeO ddg hMOg hUdhGJg Ydi SjOfG eMeO NGJe GdfHjjf hSjO GdeQSdjf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B179 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B204 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B269s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3eMeO Hf YHO GdQMef GdYHjcGf GdNGUI HGdQjGV(B(953/ 223) s
Keywords: (3GdJGQjNs